Predictors of infection in chronic lymphocytic leukaemia (CLL). - Griffiths, H (1992)
A group of patients with chronic lymphocytic leukaemia (CLL) were studied to determine whether particular clinical and laboratory parameters might help to identify those patients at risk of recurrent infection who would benefit from immunoglobulin replacement therapy. The case notes of 59 patients were reviewed with regard to stage and duration of disease, chemotherapy and frequency of infection over the preceding 2 years. Serum IgG levels and specific antibodies to tetanus, diphtheria and pneumococcal capsular polysaccharide were measured at the end of the 2-year period. A group of 56 healthy age-matched volunteers were used as controls. Eighteen patients had severe or multiple infections during the study period, 11 patients had recurrent infections and the remaining 30 patients had only minimal infections. Overall, serum IgG levels were low in 32 patients but in none of the control group (P = 8.8 x 10(-11). However, less than half of those patients with hypogammaglobulinaemia suffered from severe or multiple infections. Specific antibodies to pneumococcal capsular polysaccharide were low in 23 patients compared with six of the control group (P = 4.9 x 10(-4)). The majority of patients with severe or multiple infections (13/18) had low levels of both total IgG and specific antibodies to pneumococcal capsular polysaccharide. However, in the groups of patients with less frequent infections, a higher proportion had low serum IgG than low pneumococcal antibody levels. Low levels of pneumococcal antibodies were particularly associated with severe or multiple infections (P = less than 0.00001).